Influência das variáveis de processamento na cor e propriedades tecnológicas de cerâmicas estruturais - Feitosa, Alan de Oliveira (2015)
The color obtained after the burning step of structural ceramics is a feature that can be a determining factor in choosing the final product by the consumer which appears increasingly discerning, demanding the provision of more uniform products, always associating the aesthetic aspects to the technological properties product. Research that attempts to correlate the color variables of the ceramic pieces to their technological properties, thereby aiding the production process at structural ceramics industry, there are no. In this sense the main objective of this work is to study the possible variables that influence the formation of the color of the structural ceramics as well as associate the color variations and shades the technological properties of the ceramic product. It developed an experimental project divided into five stages. The first step is presented throughout the collection procedure, preparation and characterization of the raw materials used. In the second stage evaluation is made of the variation of the color of the ceramic products due to the chemical composition of the samples. In step III is made the analysis of the variation in color depending on processing variables as burning temperature, hold time, burning rate and pressing conditions. In steps IV and V were evaluated respectively, the main technological properties and the microstructure of the ceramic pieces developed. The results show that the chemical composition of each raw material is largely responsible for the formation of the color of the ceramic pieces, depending on the iron oxide content present in clays. The processing variables as burning rate and pressing conditions shown to have little influence on the variation of tonality of parts as well as in their technological properties. Increasing the burning temperature promoted an accentuation in tonalities of the ceramics pieces, emphasizing the white and red colors presented by the final product, as well as caused significant variations in their technological properties, such as water absorption and apparent porosity reduced and increased apparent specific mass and flexural strength.